Pressurized entrained-flow high temperature black liquor gasification : CFD based reactor scale-up method and spray burner characterization - Marklund, Magnus (Luleå tekniska universitet, Strömningslära och experimentell mekanik, 2006)
Black liquor is an important by-product in the chemical kraft pulping process, which provides the paper mill with pulp. Due to both economical and environmental protection driving forces it is important to recover the pulping chemicals and energy contained in the black liquor. In the conventional recovery cycle, the energy is recovered as steam by combustion of the black liquor in a recovery boiler and the pulping chemicals are initially recovered as a smelt formed in the boiler. The recovery boiler has been serving the kraft pulping industry for many decades and continuous efforts have been made to improve its efficiency. However, despite these efforts the recovery boiler cycle still has a relatively low overall efficiency. A promising alternative recovery technology currently under development is Pressurized Entrained-flow High Temperature Black Liquor Gasification (PEHT-BLG). By introducing PEHT-BLG in the mill’s recovery cycle the flexibility in the energy and chemical recovery is greatly enhanced. The syngas obtained from the process can be used to generate electricity or be reformed into chemicals, e.g. bio-fuels for transportation. The sulfur species in the syngas can be converted to pure sulfur and thereby open up possibilities for alternative pulping methodologies Lack of demonstration of the reliability of the PEHT-BLG technology has delayed a large scale industrial implementation of the process. In order to remedy this situation and to obtain proof on reliability and deepen the insight in the PEHT-BLG process, a development plant (DP-1) has since late 2005 been operating periodically by the technology vendor Chemrec AB at the laboratory of Energy Technology Centre in Piteå, Sweden. In order to aid in future scale-up needs, the main objective of the applied research work presented in this thesis has been to develop a comprehensive CFD model of the black liquor conversion process for the PEHT-BLG reactor. In addition, work has also been performed in order to develop a suitable methodology for spray ...